Integrated deposition and machining of aluminium alloy using WAAM - Qiao, Liuping (Cranfield University, 2013)
Conventional manufacturing processes often require a large amount of machining and cannot satisfy the continuously increasing requirements of a sustainable, low cost, and environmentally friendly modern industry. To solve these problems, Wire and Arc Additive Manufacturing (WAAM) process is used, which has a much higher deposition rate than most other metal additive manufacture processes. Integrated deposition and machining is a novel AM technique which combines deposition and milling in one process; the milling step on the top surface does not only ensure the fixed height increment of each layer, but also increases the surface quality of the deposited multi-layered structure. In addition, the internal and external surface profile can be machined to remove any remaining surface roughness to attain the desired high quality surface of a near-net shape metal part. In this project, the research aims at integrating WAAM technology with subtractive technology using basic wall shaped part structures in the analysis for finding the relationship between milling amount, surface waviness and part fatigue life. The project also applied the integrated deposition and machining (milling & drilling) idea to introduce a new way of deep hole drilling, especially for small-dimensional deep holes, which can be used to structures that would be impossible to attain by traditional hole drilling methods.
Keywords: Wire and arc additive manufacturing; Integrated deposition and machining; Dry machining; Near net shape; Small-dimensional deep hole drilling